Atuação profissional do agente de inclusão escolar: um estudo sobre os sentidos e significados constituídos por um deles - Carvalho, Agda Malheiro Ferraz de (2016)
The aim of this study was to gain knowledge about the professional practice of school inclusion agents (SIAs), in order to understand the senses and meanings constructed by one of them about his job. It is worth mentioning that the term SIAs refers to persons that provide assistance and care to students with disabilities attending regular schools. The research was conducted in a small county near the city of São Paulo (SP), where the SIA (Joseph) was interviewed. The data was recorded, transcribed, systematized and analyzed following the proposal of Aguiar and Ozella (2006, 2013) and Aguiar, Machado and Soares (2015), authors linked to the Sociocultural Psychology. It was found that Joseph came to the profession through public tender, with little information about what his task should be. Doing it, he came to realize the need to improve his interventions with the students, so that they could be active participants in the teaching-learning-evaluation process. The respondent s many frustrations seem to arise from the ambiguity between what he does and what he believes he should do, since he perceived the difficulties faced by students with disabilities and also those involved in dealing with them. Thus, the understanding of what is to be and to act as an SIA can help to better define what is expected of them in terms of providing support and education to students with functional differences, an essential feature of a truly inclusive education